The Role of Social Risk Factors in Dialysis Quality and Patient Outcomes Under a Medicare Quality Incentive Program. Issue 10 (26th October 2022) - Breck, Andrew; Marr, Jeffrey; Turenne, Marc; Esposito, Dominick
Abstract : Background: There have been critical improvements in dialysis care and mortality in the last decade. These improvements track with the implementation of the end-stage renal disease (ESRD) Quality Incentive Program (QIP) beginning in 2012, which aligns Medicare payments to dialysis facilities with performance on quality measures. This study explores whether the improvements in dialysis care and patient outcomes under the ESRD QIP have been shared equally among patient groups. Methods: Our analyses focus on 4 social risk factors: Black race, Hispanic ethnicity, dual eligibility for Medicare and Medicaid, and rurality. We estimated multivariable regressions using longitudinal Medicare and Consolidated Renal Operations in a Web-Enabled Network data. Results: ESRD QIP payment reductions were more common at dialysis facilities with higher proportions of Black and dual-eligible ESRD patients. Patients with dual eligibility and Black race had persistently worse relative outcomes as the ESRD QIP was implemented. This finding was true for differences in outcomes when comparing patients within and across facilities and was not affected by the addition of specific quality measures to the ESRD QIP measure set. Hispanic patients and patients at rural facilities have generally not had worse outcomes since the start of the ESRD QIP. Conclusions: There is no evidence of widening disparities in dialysis care or patient outcomes across patient groups under the ESRD QIP, which is a longstanding and well-publicized concern with value-based purchasing programs. Relative changes between patient groups since the start of ESRD QIP have not favored any patient group. Many disparities in dialysis quality measures and assessment of dialysis facility payment reductions persist.